Criminal Liability of Bank Officials in Fictitious Loan Cases: A Study of Court Decisions - Samosir, Parulian; Karina, Ica (PALAR (Pakuan Law review), 2025)
Fictitious credit cases are a form of banking crime that often involves bank officials who have authority in the credit analysis, approval, and disbursement process. This research aims to analyse the form of criminal liability for bank officials in fictitious credit cases and to assess the basis for the judge's considerations in determining the guilt, role, and criminal sanctions against the perpetrators. The research method used is normative legal research with a case study approach through the analysis of several court decisions related to the criminal act of fictitious credit. The research findings indicate that bank officials can be held criminally liable based on proof of abuse of authority, gross negligence, or active involvement in the creation of credit documents and data that do not comply with internal bank regulations or legislation. The judge's considerations generally focus on the element of intent, position held, and the impact of the losses on the bank's and customers' finances. This research underscores the importance of strengthening internal oversight mechanisms, enhancing the integrity of bank officials, and updating banking regulations to prevent the recurrence of similar crimes.